2019
DOI: 10.2131/jts.44.871
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> genotoxicity analyses of colibactin-producing <i>E. coli</i> isolated from a Japanese colorectal cancer patient

Abstract: Colibactin is a polyketide-peptide genotoxin produced by enteric bacteria such as E. coli, and is considered to contribute to the development of colorectal cancer. We previously isolated E. coli strains from Japanese colorectal cancer patients, and in the present study we investigated the genotoxic potency of the colibactin-producing (clb +) E. coli strains that carry the polyketide synthases "pks" gene cluster (pks +) and an isogenic clbmutant in which the colibactin-producing ability is impaired. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Escherichia coli from the B2 phylogenetic group possesses a genomic island named polyketide synthetase ( pks ), which is thought to produce a polyketide‐peptide genotoxin, colibactin. E coli containing pks ( pks + E coli ) has been shown to induce DNA double‐strand breaks, cell cycle arrest, mutations, and chromosomal instability in eukaryotic cells 6‐9 . Colibactin also alkylates DNA in vivo and DNA adducts have been identified in mammalian cells and mice exposed to pks + E coli 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli from the B2 phylogenetic group possesses a genomic island named polyketide synthetase ( pks ), which is thought to produce a polyketide‐peptide genotoxin, colibactin. E coli containing pks ( pks + E coli ) has been shown to induce DNA double‐strand breaks, cell cycle arrest, mutations, and chromosomal instability in eukaryotic cells 6‐9 . Colibactin also alkylates DNA in vivo and DNA adducts have been identified in mammalian cells and mice exposed to pks + E coli 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity island encoding colibactin, known as polyketide synthase (pks), are detected in up to 66.7% of CRC patients (Arthur et al, 2012). Moreover, experimental studies show that colibactin could sustain tumor growth by generating DNA cross links in cellulo, which were later transformed into DNA doublestrand breaks (Bossuet-Greif et al, 2018;Kawanishi et al, 2019;Wilson et al, 2019), or by favoring the emergence of senescent cells (Cougnoux et al, 2014;Dalmasso et al, 2014). Senescent cells are cells with an irreversible cell cycle arrest.…”
Section: Fats Bile Acidsmentioning
confidence: 99%
“…U.S.A). The DNA damaging potency of bacterial cell extracts was estimated using the umu test, as previously described [5]. Briefly, E. coli cells were harvested from 10 mL of overnight culture in LB media (O.D.…”
Section: E Coli Strains and Genotypingmentioning
confidence: 99%
“…The clb + E. coli stimulates growth of colon tumors under conditions of host inflammation, and is found with increased frequency in inflammatory bowel disease, familial adenomatous polyposis, and colorectal cancer patients [2,3]. We previously reported that E. coli strains isolated from a Japanese colorectal cancer patient produced colibactin and showed genotoxicity in in vitro assays [4,5]. However, the chemical structure of the genotoxin, the molecular mechanism of its mutagenesis/carcinogenesis, and distribution of the clb gene cluster among microorganisms have not been fully clarified yet.…”
Section: Introductionmentioning
confidence: 99%